2017
DOI: 10.15282/ijame.14.3.2017.13.0360
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive wear behaviour of aluminium hybrid nanocomposites produced by ultrasonication assisted casting method

Abstract: In this investigation, the abrasive wear resistance of Al/ (B4C+SiC) hybrid nanocomposites was tested against hard SiC abrasive sheets and compared to those of unreinforced Al alloy. Three loadings of nano-SiC (0.5, 1.0, and 1.5 Wt. %) and one loading of nano-B4C (0.5 Wt. %) were mixed with an aluminium alloy to produce the aluminium hybrid nanocomposites using an ultrasonication assisted casting method. Scanning electron microscopy showed a uniform distribution of nanoparticles in the Al alloy. Transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Wear resistance was significantly improved for samples containing 0.5 wt% B 4 C and 1.5 wt% SiC compared with aluminum. The coefficient of friction was in the expected range for all samples [14]. Except for coconut shell and coconut fiber, all fibers were treated chemically to enhance their properties.…”
Section: Coarse Finementioning
confidence: 91%
See 3 more Smart Citations
“…Wear resistance was significantly improved for samples containing 0.5 wt% B 4 C and 1.5 wt% SiC compared with aluminum. The coefficient of friction was in the expected range for all samples [14]. Except for coconut shell and coconut fiber, all fibers were treated chemically to enhance their properties.…”
Section: Coarse Finementioning
confidence: 91%
“…The wear particles whose diameter is less than 100 nanometers Fused mullite (i) Density reduced from 6.2 g/cc to 2.40-2.72 g/cc for three different samples (ii) The wear rate for the sample containing 3 wt% of mullite decreased from 1 g to 0.887 g [88] Nanosized SiO 2 particles (i) With the addition of 9% SiO 2 , there was an improvement of 18.11% in hardness & an increase of 5.4% in roughness [12] Phenolic resin (PF)/organized expanded vermiculite (OEVMT) (i) The brake pad based on PF exhibited a weight reduction ratio of 45.8%, whereas the brake pad based on PF/OEVMT exhibited a ratio of 77.1% (ii) For the PF/OEVMT brake pad, the coefficient of friction decreased by only 0.05, whereas for the PF based brake pad, the value decreased by 0.24 [39] Kaolin-TiO 2 (KATI) (i) The loss of pad thickness was 50% lower for the KATI-based brake pad which improved the durability [13] Boron (i) The coefficient of friction for the boron-based brake pad was 0.065 higher than its counterpart [41] Graphene/boron nitride with aluminum (i) Sample Al-1BN-0.15GNP exhibited an increase of 225% in ultimate compressive strength & an 87% increase in hardness values [42] Aluminum-silicon nitride (Al-Si 3 N 4 ) & aluminum-graphite-silicon nitride (Al-Gr-Si 3 N 4 ) (i) For the Al-Gr-Si 3 N 4 sample, the wear rate decreased by 25% when compared with the Al-Si 3 N 4 sample (ii) There was a reduction of 15% in the friction coefficient of the Al-Gr-Si 3 N 4 sample when compared with the Al-Si 3 N 4 sample [45] Al/SiC+B 4 C (iii) Wear resistance increased by 88.32% for the sample containing 1.5% SiC & 0.5% B 4 C as compared with a monolithic aluminum [14] 14 Journal of Nanomaterials method revealed that BP10 samples had the highest wear rate, whereas BP5/BG5 samples depicted the lowest values [38]. Superior thermal characteristics of the PF/OEVMTbased brake pad were confirmed by thermogravimetric analysis.…”
Section: Brake Pad Wear Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…AMMCs reinforced with SiC particles enhance yield strength by up to 20%, lower thermal expansion coefficient, higher elasticity modules and greater wear resistance compared to unreinforced matrix alloy systems [5][6]. The B4C reinforced AMMCs are harder, tougher, more fracture-resistant, lighter in weight and have higher fatigue strength and significantly improve properties compared to other materials.…”
Section: Introductionmentioning
confidence: 99%